LARGE SIZE LIQUID PSC PARTICLES OBSERVED OVER NY-ALESUMD - シバタ, タカシ; イワサカ, ヤスノブ; フジワラ, モトオ; ハヤシ, マサヒコ; ナガタニ, マサヒロ; シライシ, コウイチ; アダチ, ヒロシ; サカイ, テツ; ススム, カズミ; ナクラ, ヨシノブ; SHIBATA, Takashi; IWASAKA, Yasunobu; et al. (National Institute of Polar Research, 1997)
P(論文) Polar stratospheric clouds (PSCs) were observed by lidar at Ny-Alesund, Spitsbergen in December 1994 and January 1995. The backscattering coefficient at wavelengths of 1064nm and 532nm, and the depolarization ratio of PSCs at 532nm, were measured by the lidar system. The stratospheric temperature from mid-December to mid-January was below the estimated frost point of nitric acid tri-hydrate (NAT) in winter 1994/1995. PSCs were observed more frequently in this low temperature period than in previous winters since 1991. The characteristics of the PSCs observed by lidar were very variable, but had a noticeable vertical "sandwich" structure in January in which a layer of liquid PSC particles at altitude around 20km existed between two solid particle layers. The wavelength dependence of the backscattering shows that the size of both liquid and solid particles was larger than the average size of background stratospheric aerosols. Lidar observations of liquid layer particles show characteristics in qualitative agreement with those expected from model PSC particles grown in ternary solutions of H_2SO_4,HNO_3,and H_2O with a temperature decrease. However, the observed backscattering coefficient and its wavelength dependence indicate that PSC particles require further growth than that predicted by the ternary solution model at temperature at which most HNO_3 molecules in the surrounding atmosphere are considered to be condensed on PSCs. departmental bulletin paper